Guidebook for developing pedestrian and bicycle performance measures. - (:unkn) unknown (My University, 2016)
This guidebook is intended to help communities develop performance measures that can fully integrate pedestrian and bicycle planning in ongoing performance management activities. It highlights a broad range of ways that walking and bicycling investments, activity, and impacts can be measured and documents how these measures relate to goals identified in a community's planning process. It discusses how the measures can be tracked and what data are required, while also identifying examples of communities that are currently using the respective measures in their planning process. This report highlights resources for developing measures to facilitate high quality performance based planning.
Keywords: Individualverkehr; Fahrradverkehr; Fußgängerverkehr; Verkehrssicherheit; Verkehrsplanung